(untitled) (TEL Tempo, Espaço e Linguagem, 2024)
The article seeks to highlight the relation between emotions and affect and sociopolitical practices, and to develop modes of theorization by centralizing affects, rejecting the rationality/emotion separation. Taking the protests of the Lastesis Collective (2019) as a case study, we propose their action as a diagnosis of relational and embodied political dynamics in which women are involved. Using emotions and affects as an analytical lens, the article explores three emotions: anger, fear, and love.